Waste Bank Program for Households as A Means of Processing Inorganic Waste - Anna Maria Sri Asih; Fitri Trapsilawati; Bertha Maya Sopha; Nur Mayke Eka Normasari (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2022)
Waste management is crucial in the present day, particularly due to the increase in trash production caused by population growth. To address this issue, the government has implemented the Waste Bank Program, which aims to reduce the amount of waste stored at disposal sites. This program has had a significant impact on the management of household waste, which makes up the majority of all waste generated in Indonesia. Despite its importance, participation in the Waste Bank program is low in many communities. To address this issue, a community activity was organized in Sleman, Yogyakarta Special Region to promote and implement the Waste Bank program in one of the 44-family Neighborhood Units. The focus of this activity was the management of inorganic trash. During the six-month period from April to October 2021, the Waste Bank program had a significant increase in participation, with the percentage of community members taking part rising from 27% to 60%. As a result of these efforts, a total of 1,084 kg of inorganic trash was collected. This waste was primarily composed of paper, followed by plastic, various other materials such as iron, aluminum, and used cooking oil, and a smaller amount of glass. The report summarizes the steps taken, challenges encountered, and potential solutions implemented during the initiation of the Waste Bank program. Additionally, the community was able to save 16% of the revenue generated from the collected trash through monthly environmental fees. These findings provide valuable insight into the current state of waste generation and the community’s situation, which can inform future efforts to reduce waste.